A descriptive survey of government workstations in relation to productivity of selected employees - Robles, Ma. Erissa Ann G.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT The study determined the physical characteristics of the workstation layout and the symbolic meanings of the accessories present and assessed how they affect the productivity of employees. Forty-five (45) respondents participated in the study who were chosen through purposive sampling. Respondents are employees in three (3) departments of National Housing Authority, a government agency located in Quezon City. They are permanent employees who are working for eight (8) hours a day in a primary, assigned workstation. The study employed the descriptive research design and included both qualitative and quantitative means of data gathering. Results show that the physical characteristics of the workstation layout vary according to the department because of the distinction in job functions and work styles. The kind of furniture present in the workstation are similar but there is a difference in the amount of work surface, the number of storage units and equipment. Accessories displayed in the employees' workstation also vary greatly, particularly in terms of employee's gender, job description, and number of years in the office. Accessories displayed have different symbolic meanings to the employees who display them. The employees believe that the physical characteristics of the workstation layout have an effect on their productivity if it enables them to work efficiently and comfortably. Likewise, the results of the study have showed that the symbolic meanings of the accessories present in the workstation have an effect to the productivity of employees for the reasons that the items serve as reference to work, reminder of family and other relationships, motivator, pacifier and status markers.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Microcomputer workstations -- Philippines; Office equipment and supplies -- Philippines -- Quezon City